PENGUKURAN TEORI PSIKOLOGI SASTRA ANAK TERHADAP KESESUAIAN ANTARA KARYA SASTRA ANAK DENGAN TINGKAT PSIKOLOGI PERKEMBANGAN ANAK DI SEKOLAH DASAR - Herwan FR (Jurnal Membaca Bahasa dan Sastra Indonesia, 2016)
Literature can develop children's imagination and help them consider and think about nature, experience, ideas, in various ways. Literature can also develop insights into the behavior of a human child, it can also introduce the universality of experience to children. Literature helps children toward a broader understanding of the ties, relations of mankind or humanity are common and natural. The relationship can be attributed to psikosastra as a concept study of children's literature ever developed Donna E. Norton in the book Through the Eyes of a Child: An Introduction to Children's Literature.Sebuah study long enough, it took nearly a year about the author , with the object of fifth grade elementary school students, in two different schools. Elementary school Labuan in Banten coastal areas of the South, and an elementary school in Panancangan, which is located in the center of the city of Serang, Banten. Based on the analysis of 11 literary discourse contained herein Indonesian Class V, published by the National Center of Books, akhirnyta found in an analysis, that there are six children who have a literary discourse suitability intrinsic value and extrinsic to the various theories of child development.